Building a mission in Ottoman Empire: A research on Istanbul Robert College gymnasium building in the light of new documents - Yilmaz, Tugba; Unal, Zeynep Gul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2025)
This study analyzes the strategic and operational framework of building a mission in a foreign country within the standards of local, international, and associated systems. The anatomy of the activities of the American Board of Commissioners for Foreign Missions (ABCFM, American Board), the largest missionary organization of the 19th century, is examined through the construction of Robert College and its educational system in the Ottoman capital. The construction journey of Robert College's Gymnasium Building and its architectural changes through time illustrate how the mission's visibility was achieved within the framework of Ottoman laws and the social environment in which it was situated. In this study, previous works within this scope were first examined. Then, documents accessed for the first time through research conducted at Columbia University, Rare Books and Manuscript Library, Bo & gbreve;azi & ccedil;i University Architectural Drawings Collection, and the Ottoman Archives of the State Archives Directorate were compiled (archival research continued from 27.05.2022 to 26.06.2024). Based on these documents, the Gymnasium Building was documented, and the construction process was interpreted through the existing traces and alterations on the building. In the light of the data obtained, the first section of the article will describe the permission and the construction process of Robert College. The second section will examine the environment that created the necessity for a Gymnasium building within the school and the sports activities in the Ottoman Empire in a comparative manner. In the third section, the documents obtained from various institutional archives will be published for the first time, and the processes of obtaining permissions, project planning, construction, and the material procurement for the Gymnasium Building will be analyzed. Additionally, this section will evaluate the prepared survey project and the restitution proposals concerning the archival data.
Keywords: American board; gymnasium; missionary buildings; Robert College; Rumeli Hisar & imath; Architecture